Dataset for the reporting of nephrectomy specimens for Wilms' tumour treated with preoperative chemotherapy: recommendations from the International Society of Paediatric Oncology Renal Tumour Study Group - Gordan M Vujanić (14779327) (2021)
Datasets for histopathological reporting of many cancer types are developed by the International Collaboration on Cancer Reporting (ICCR), and are used in order to ensure standardised and uniformly accepted reporting as one of the essential requirements for comparison across patient populations in evaluating and validating pathological prognostic and predictive factors. Wilms' tumours are rare, and international reporting guidelines have not yet been published by the ICCR. The assessment of Wilms' tumours differs according to the treatment approach. The Children's Oncology Group, whose approach is followed mainly in North America, advocates primary surgery, and the International Society of Paediatric Oncology Renal Tumour Study Group (SIOP-RTSG), whose approach is followed in most countries around the world, uses preoperative chemotherapy as a first step, resulting in different subclassifications, staging criteria, and histopathological prognostic factors. This dataset is developed for the countries and institutions following the SIOP-RTSG approach, and it contains core (required) and non-core (recommended) elements, based on the results of the previous SIOP-RTSG studies, which are incorporated in the latest SIOP-RTSG UMBRELLA 2016 Study protocol. The core elements include clinical information, additional specimen submitted, macroscopic tumour site and appearance, tumour focality, tumour dimensions, macroscopic extent of invasion, block identification key, histological tumour type, histological tumour grade and risk group assessment, microscopic extent of invasion, lymphovascular invasion, resection margin status, regional lymph node status, histologically confirmed distant metastases, and pathological staging (SIOP staging system). The dataset should improve communication for patient care and prognostic determination of the old and new histopathological features. Other Information Published in: Histopathology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1111/his.14394